Complexation of α-Mangostin with γ-Cyclodextrin and Its Application in Alginate/Chitosan Hydrogel Mucoadhesive Film for Treatment of Recurrent Aphthous Stomatitis - Suharyani I; Mohammed AFA; Muchtaridi M; El-Rayyes A; Abdassah M; Suhandi C; Wathoni N (Journal of Inflammation Research)
Ine Suharyani,1,2 Ahmed Fouad Abdelwahab Mohammed,3 Muchtaridi Muchtaridi,4 Ali El-Rayyes,5 Marline Abdassah,1 Cecep Suhandi,1 Nasrul Wathoni1 1Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 2Faculty of Pharmacy, Universitas Muhammadiyah Ahmad Dahlan Cirebon, Cirebon, West Java, 45153, Indonesia; 3Department of Pharmaceutics, Faculty of Pharmacy, Minia University, Minia, 61517, Egypt; 4Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 5Center for Scientific Research and Entrepreneurship, Northern Border University, Arar, 73213, Saudi ArabiaCorrespondence: Nasrul Wathoni, Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, 45363, Indonesia, Tel\Fax +6222 842 888888, Email nasrul@unpad.ac.idIntroduction: α-Mangostin (α-M), one of the xanthon compound isolated from Garcinia mangostana rind, demonstrates the efficacy in the treatment of recurrent aphthous stomatitis (RAS). The lack of solubility of α-mangostin in water limited its pharmacological application.Purpose: The lack of solubility of α-mangostin in water limited its formulation and pharmacological application. This study was done to enhance the solubility of α-M by complexation with γ-cyclodextrin (γ-CD) and its application in Alginate/Chitosan Hydrogel Mucoadhesive Film (HMF) for RAS treatment.Methods: This complex was made by dissolved α-M and γ-CD in separated solution. α-M solution gradualy added into γ-CD to formed α-M/γ-CD complex (α-M/γ-CD CX). This complex then evaporated to yield the dry complex powder. The complex was successfully formulated into hydrogel mucoadhesive film (HMF) preparations based on characterization using Scanning Electron Microscope (SEM), Fourier Transform Infra-Red (FTIR), and X-Ray Diffractometry (XRD). The complex was formulated in hydrogel mucoadhesive film, followed by in-vitro drug release and the study of recurrent aphthous stomatitis (RAS) activity in rats.Results: The α-M/γ-CD CX HMF film has a higher mucoadhesive force and mucoadhesive time than other HMFs resulting in a prolonged retention time in the oral mucosa. The drug release of α-M/γ-CD CX HMF followed the Korsmeyer-Peppas Model with a total amount of drug released 80.34+0.32%. The inclusion complex of α-M/γ-CD CX HMF exhibited increased anti-RAS activity compared to HMF base, α-M HMF, and α-M/γ-CD PM HMF. This was evidenced by a significant decrease in wound area of approximately 79.05± 3.30%, an increase in epithelial thickness of about 1.24± 0.09 μm, and a decrease in neutrophil score 1.10± 0.26. These findings highlight the potential use of α-M/γ-CD CX as an effective RAS agent in HMF.Conclusion: The complex of α-M/γ-CD CX has improved solubility of α-M, resulting in the transparent and homogenous film. The film containing this complex has the better physical characteristic, increasing the release and RAS activity. Keywords: α-Mangostin, γ-cyclodextrin, inclusion complex, solubility, hydrogel mucoadhesive film, recurrent aphthous stomatitis